Anxiety sensitivity: Changes with puberty and cardiovascular variables. Issue 1 (5th November 2014) - Akça, Ömer Faruk; Ağaç Vural, Tuba; Türkoğlu, Serhat; Kılıç, Emine Zinnur
Abstract Background Anxiety sensitivity (AS) is a relatively stable dispositional variable that may increase the risk for anxiety‐related symptoms, particularly panic attack, among individuals of all age groups. Changes in AS during adolescence in healthy individuals, however, has not been previously investigated. The aim of this study was therefore to investigate the relationship of AS with puberty level, pulse rate, and blood pressure in healthy adolescents. Methods The sample consisted of 133 healthy adolescents (70 boys, 63 girls) aged 10–17 years. Puberty stage (i.e. Tanner stage), pulse rate, and blood pressure of each participant were determined. The Childhood Anxiety Sensitivity Inventory was used to identify AS. The correlations between AS and the clinical variables were assessed. Results AS was negatively correlated with pubertal stage when age and gender were controlled. Also, AS was correlated with diastolic blood pressure when age, gender, and pubertal stage were controlled (P < 0.05). Neither systolic blood pressure nor heart rate were correlated with AS. Conclusion AS, which is reported to be a trait‐like variable, may change during adolescence, due to the effect of pubertal growth and blood pressure interacting with AS during adolescence.